Tuning the Coherent Propagation of Organic Exciton‐Polaritons through Dark State Delocalization. Issue 18 (27th April 2022) - Pandya, Raj; Ashoka, Arjun; Georgiou, Kyriacos; Sung, Jooyoung; Jayaprakash, Rahul; Renken, Scott; Gai, Lizhi; Shen, Zhen; Rao, Akshay; Musser, Andrew J.
Abstract: While there have been numerous reports of long‐range polariton transport at room‐temperature in organic cavities, the spatiotemporal evolution of the propagation is scarcely reported, particularly in the initial coherent sub‐ps regime, where photon and exciton wavefunctions are inextricably mixed. Hence the detailed process of coherent organic exciton‐polariton transport and, in particular, the role of dark states has remained poorly understood. Here, femtosecond transient absorption microscopy is used to directly image coherent polariton motion in microcavities of varying quality factor. The transport is found to be well‐described by a model of band‐like propagation of an initially Gaussian distribution of exciton‐polaritons in real space. The velocity of the polaritons reaches values of ≈ 0.65 × 10 6 m s −1, substantially lower than expected from the polariton dispersion. Further, it is found that the velocity is proportional to the quality factor of the microcavity. This unexpected link between the quality‐factor and polariton velocity is suggested to be a result of varying admixing between delocalized dark and polariton states. Abstract : Coherent energy transport is directly measured in a family of organic microcavities containing exciton‐polaritons, using femtosecond transient microscopy. It is found that the quality of the cavity structure impacts both the range and, surprisingly, the velocity of transport. This unexpected effect can be explained through the involvement of delocalized intracavity dark states, which are directly impacted by the cavity quality.